The Influence of Green Marketing and Digital Marketing on the Competitiveness of MSMEs Tempeh Chips in Malang City with Brand Image as a Mediating Variable - Jauharotun NAFISAH; Aldina SHIRATINA (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This research aims to analyze the effect of green marketing and digital marketing on the competitiveness of MSMEs mediated by brand image. The object of this research is MSME players in the tempeh chips sector in Malang City, with data collected from 150 respondents. This research uses a quantitative approach. Sample measurement in this study used saturated sampling technique with SmartPLS 4.0 analysis tool. The results showed that green marketing has a positive and significant effect on brand image. Digital marketing has a positive and significant effect on brand image. Brand image is also proven to have a positive and significant effect on the competitiveness of MSMEs. Green marketing mediated by brand image has a positive effect on competitiveness. Digital marketing mediated by brand image has a positive effect on competitiveness. Researchers recommend that tempeh chips MSMEs in Malang City optimize digital communication tools, strengthen branding strategies, set prices according to product added value, and implement environmentally friendly practices. Future research is recommended to consider other variables that affect MSME competitiveness and adopt a multi-method approach for more comprehensive insights.